Spatial Diversity of Biotechnology Centres in Germany - Dorocki, Sławomir (Quaestiones Geographicae, 2014)
The growth of this sector in Germany began later than in the USA or other West European countries. But, thanks to the regional policy pursued by the state stimulating the development of biotechnology clusters, in a period of fifteen years or so, Germany has become the global leader. This paper presents the process of developing biotechnology centres in Germany as well as their spatial distribution, accompanied by their short description.